An Evaluation of the Effect of Using Irrigations at Different Temperatures on Pain, Edema, and Trismus during the Extraction of Bilateral Impacted Mandibular Third Molars: A Randomized Split-Mouth Clinical Trial - Dayanan, C.; Ozupek, Mf; Seyrek, Nk (Wolters Kluwer Medknow Publications, 2023)
Background and Aim: The surgical extraction of impacted wisdom teeth is a standard practice in dentistry. Unfortunately, inflammatory reactions such as discomfort, edema, and trismus frequently jeopardize patients' well-being after the extraction of third molars. Saline solutions at room temperature (25 degrees C) are routinely used in impacted tooth extraction. Refrigerated saline solutions were used to work with cold solutions, and as the refrigerator temperature was 4 degrees C, this study was designed to have a cold solution temperature of 4 degrees C. This study aimed to assess the influence of saline irrigation at various temperatures (4 degrees C, 25 degrees C) on postoperative edema, pain, and trismus after the extraction of impacted third molars. Materials and Methods: Eighteen patients with bilateral symmetrical mandibular impacted third molars were enrolled in this split-mouth, randomized, prospective, double-blind clinical trial. For each patient, one side was irrigated with a saline solution (% 0.9 isotonic sodium chloride) at 4 degrees C (test), and the other side was irrigated with a saline solution at room temperature (25 degrees C) (control). Pain, trismus, and facial edema were noted on the 2nd, 4th, and 7th days. A Mann-Whitney U-test was used to compare pairs, and a Wilcoxon signed-rank test was used to compare groups. Results: The two groups had no considerable differences in terms of pain levels and facial edema (P > 0.05). Regarding trismus, the maximum mouth opening for cold irrigation (4 degrees C) was significantly higher than for room temperature irrigation (25 degrees C) across all postoperative periods (P < 0.05). Conclusion: Cold irrigation therapy (4 degrees C) exerts beneficial effects more than room temperature (25 degrees C) irrigation on the trismus after impacted mandibular third molar surgery.
Keywords: Irrigation; postoperative morbidity; temperature; third molar surgery